Correction: The selective hydrosilylation of norbornadiene-2, 5 by monohydrosiloxanes. Issue 60 (30th October 2019) - Guseva, Marina A.; Alentiev, Dmitry A.; Bermesheva, Evgeniya V.; Zamilatskov, Ilya A.; Bermeshev, Maxim V.
Abstract : Correction for 'The selective hydrosilylation of norbornadiene-2, 5 by monohydrosiloxanes' by Marina A. Guseva et al., RSC Adv., 2019, 9, 33029–33037.